2014
DOI: 10.7314/apjcp.2014.15.17.7351
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Neutrophil-to-Lymphocyte Ratio in Squamous Cell Carcinoma of Larynx Compared to Benign and Precancerous Laryngeal Lesions

Abstract: Background: Laryngeal carcinogenesis is a multifactorial process that has not been fully elucidated. Despite extensive research, reliable markers with diagnostic and prognostic value are still lacking. It was recently reported that an elevated preoperative neutrophil-to-lymphocyte ratio (NLR) may correlate with an increased risk of recurrence, tumor aggressiveness and poorer prognosis in various malignancies. The aim of this study was to examine whether NLR could be used as an inflammatory marker to differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
68
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 29 publications
4
68
0
3
Order By: Relevance
“…[11,12] According to recent studies, elevated PLR and NLR values were associated with poor survival in different solid tumors. Kum et al [13] found statistical significance between the NLR values and the groups in the study conducted with 209 patients by studying three groups of benign, premalignant, and malignant lesions. In their study of 141 patients, Tu et al [14] found that elevated preoperative NLR was an independent predictor for poor prognosis after surgical resection in patients with LSCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11,12] According to recent studies, elevated PLR and NLR values were associated with poor survival in different solid tumors. Kum et al [13] found statistical significance between the NLR values and the groups in the study conducted with 209 patients by studying three groups of benign, premalignant, and malignant lesions. In their study of 141 patients, Tu et al [14] found that elevated preoperative NLR was an independent predictor for poor prognosis after surgical resection in patients with LSCC.…”
Section: Discussionmentioning
confidence: 99%
“…[13,14] To the best of our knowledge, this is the first study to suggest that PLR maybe used for PLL and LSCC discrimination. According to the current results PLR may be used for PLL and LSCC discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…This facilitates tumoral growth and the development of resistance to apoptosis (Jaiswal et al, 2000;Kacan et al, 2014;Kum et al, 2014). The NLR is a well-known marker of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in this ratio is an important indicator of elevated systemic inflammation. Previous research reported that a high NLR value was a poor prognostic factor in various cancers (Kum et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation